Recursos educativos digitales en el aprendizaje de la Lengua y Literatura del séptimo grado “A”, de la Unidad Educativa José Ángel Palacio - Lozano Saca, María Celia (2022)
Digital educational resources are innovative means for educational processes, their implementation facilitates teaching and knowledge acquisition. This research has as general objective to determine the incidence of digital educational resources in the learning of Language and Literature in the seventh grade; additionally, as specific objectives to diagnose the learning of Language and Literature; additionally, to plan and execute an alternative proposal using digital educational resources to improve the learning of Language and Literature; and, to evaluate the incidence of digital educational resources; for its fulfillment it was necessary to support bibliographically thematic related to digital educational resources and the learning of Language and Literature. The methods used were: scientific, descriptive, inductive, deductive, analytical, synthetic, statistical; to obtain the information, the teacher in charge of the class, was interviewed, while and a diagnostic evaluation and a structured survey were applied to the students. The results of the diagnostic evaluation allowed to determine that 58% of the students reach the required learning, however, 42% do not reach this value scale; to counteract these deficiencies that students have in the learning of Language and Literature, an alternative proposal called "Learning by playing Language and Literature with digital educational resources" was designed and applied, where various activities were implemented by using Educaplay, Edpuzzle, Kahoot, liveworksheets, wordwall, with the active participation of the students. Then a summative evaluation was applied to assess its impact where significant progress was observed, i.e. 81% of students improved in this subject. Finally, it is concluded that the correct use of digital educational resources in the classroom improves in a positive way the learning of Language and Literature. Key words: Digital education, didactic resources, digital resources, games on platforms.